TO EVALUATE THE FUNCTIONAL OUTCOME IN PATIENTS WITH FLOATING KNEE WHO UNDERWENT MAGNETIC RESONANCE IMAGING - AGARWAL, SAUMYA; SINGH, HARPREET; ANAMENDRA SHARMA; KALIKA GUPTA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The incidence of floating knee injuries has traditionally been underestimated. However, with the increased use of magnetic resonance imaging (MRI) and arthroscopy, their frequency has risen. There is a crucial need to classify this complex injury pattern by also considering associated soft-tissue injuries. Soft-tissue injuries might be missed during clinical examination due to tenderness and swelling but can be detected through immediate MRI scans. This study aimed to evaluate the functional outcomes of patients with floating knee injuries who underwent MRI for soft tissue injuries. Methods: This study was conducted at a tertiary care center from February 2021 to January 2024. The study involved 100 patients with floating knee injuries who underwent MRI assessments for soft-tissue injuries. Follow-ups were scheduled at 1 month, 3 months, 6 months, and 1 year, with a maximum follow-up duration of 2½ years. The outcomes of floating knee injuries were assessed using the Karlstrom Olerud criteria. Results: Among 100 patients with floating knee injuries who underwent MRI, 72 had meniscus or ligament injuries, and nine had patellar fractures with extensor mechanism rupture. According to the Karlstrom Olerud criteria, seven patients had excellent outcomes, 46 had good outcomes, 33 had fair outcomes, and six had poor outcomes. Eight patients were lost to follow-up. Conclusion: Our aim is to ensure timely and accurate treatment by thoroughly addressing all associated injuries, including often-overlooked ligament damage around the knee. To improve clinical outcomes, we recommend a multidisciplinary approach involving various specialists in the care of these patients.